2004
DOI: 10.1186/1471-2458-4-59
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among general practitioners age and patient load in the prediction of job strain, decision latitude and perception of job demands. A Cross-sectional study

Abstract: Background: It is widely recognized and accepted that job strain adversely impacts the workforce. Individual responses to stressful situations can vary greatly and it has been shown that certain people are more likely to experience high levels of stress in their job than others. Studies highlighted that there can be age differences in job strain perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Therefore, the more patients professionals see every day, the greater their A-State will be. Thus, (1) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the more patients professionals see every day, the greater their A-State will be. Thus, (1) .…”
Section: Discussionmentioning
confidence: 97%
“…From this study, it was possible to understand better the emotional aspects of the nursing team facing terminality and cancer, issues that lead to anxiety and stress (1,4) . However, it is important to highlight that this study presents limitations: first, it represents the experience of a single Cancer center, although it is a reference in the State of Rio Grande do Norte; another aspect is the refusal of some professionals to take part in the study, because they had no time.…”
Section: Discussionmentioning
confidence: 99%
“…Number of studies has been argued that general practice has become an increasingly stressful place to work [2-11] by the increasing demands and constraints [6,9,12-17]. It is showed that about half of the investigated general practitioners (GP's) were not satisfied with their work [18-22] due to high job requirements.…”
Section: Introductionmentioning
confidence: 99%
“…It is showed that about half of the investigated general practitioners (GP's) were not satisfied with their work [18-22] due to high job requirements. In recent literature important sources of psychosocial stress for GP's are mentioned: excessive paperwork, health reforms, bureaucratic interference (6), job demands, decision latitude [9], workplace location [23] job pressure, patient load [6,18,24,25], lack of organizational support [26-30], dealing with difficult patients [31,32] and objective personal characteristics such as age, gender and workers marital status [33-36]. …”
Section: Introductionmentioning
confidence: 99%
“…There are several models to assess job stress including demand-control-support model that is described as the combined effects of high workload demands with low decision latitude (1). In this regard, stress has been considered as a risk arising from working environment, and as a relationship between working demands and personal abilities to cope with these demands (2).…”
mentioning
confidence: 99%